A Review of Abul Kalam Azad’s Commentary on the Qur'an, “Tarjumān Al-Qur’ān” - Muhammed Rashid Jalaly (al-Bunyan: Interdisciplinary Journal of Qur'an and Hadith Studies, 2024)
Since its earliest revelation, the Qur'an has continued to serve as Muslims' primary source of intellectual inspiration and contemplation. With the help of the Qur'an, the Prophet helped his companions modify their perspectives. In addition to reciting the Qur'an to his companions, the Prophet also used to explain its meaning to them. The guidelines for reading the Qur'an were created to enlighten future generations on how their forefathers arrived at a certain interpretation so that they wouldn't overlook the problems unique to their own eras. Among the distinguished Qur'anic exegetes that India has produced, Abul Kalam Azad has a noteworthy position. It is an Urdu commentary on the Qur'an written by Azad between 1915 and 1945, a turbulent time when he was imprisoned by the British government multiple times for extended periods of time. In the lengthy list of his writings on many themes, his Tarjumān al-Qur’ān is actually his Magnum Opus. The most notable contribution to Islamic scholarship made by Abul Kalam Azad was Tarjumān al-Qur’ān, a sincere endeavour to explain the message as it was understood by the Prophet Muhammad's (PBUH) followers’ during his lifetime. According to him, commentators in more recent times have diverted from the previous accurate understanding under the influence of foreign culture and ideas. It is more detailed than a simple translation, but it is by no means complex. One of the greatest translations of the Quran was considered by Arabic academics to be the original "Tarjumān al-Qur’ān " Maulana Azad was a renowned Arabic scholar who was well-known throughout the Muslim world in addition to being a freedom fighter and national leader. Everyone agrees that Maulana's greatest work is the Tarjumān al-Qur’ān. In doing so, he has attempted to give the Qur'anic text its intended meaning—or the interpretation that the Prophet's followers had during his lifetime—or the meaning that it originally intended to have. It takes the form of a translation of the Qur'an with explanations, accompanied where appropriate by footnotes and comments. This study goes on the library mode of data analysis. The literary masterwork of Maulana Abul Kalam Azad in Urdu, Tarjumān al-Qur’ān, has been translated into several languages and is known for standing out above other comments of a similar nature.